On animals [large type] - Orlean, Susan (Thorndike Press large print nonfiction, 2021)
'How we interact with animals has preoccupied philosophers, poets, and naturalists for ages,' writes Susan Orlean. Since the age of six, when Orlean wrote and illustrated a book called Herbert the Near-Sighted Pigeon, she's been drawn to stories about how we live with animals, and how they abide by us. Now, in On Animals, she examines animal-human relationships through the compelling tales she has written over the course of her celebrated career. These stories consider a range of creatures, the household pets we dote on, the animals we raise to end up as meat on our plates, the creatures who could eat us for dinner, the various tamed and untamed animals we share our planet with who are central to human life. In her own backyard, Orlean discovers the delights of keeping chickens. In a different backyard, in New Jersey, she meets a woman who has twenty-three pet tigers--something none of her neighbors knew about until one of the tigers escapes. In Iceland, the world's most famous whale resists the efforts to set him free; in Morocco, the world's hardest-working donkeys find respite at a special clinic. We meet a show dog and a lost dog and a pigeon who knows exactly how to get home.